Secondary metabolites and their bioactivities from Paecilomyces gunnii YMF1.00003 - Li, Su-Su; Qu, Shuai-Ling; Xie, Juan; Li, Dong; Zhao, Pei-Ji (Frontiers in Microbiology, 2024)
Four new polyketides (1-4) and seven known compounds (5-11) including three polyketides and four sterols were isolated from the fermented extracts of Paecilomyces gunnii YMF1.00003. The new chemical structures were determined through the analysis of the nuclear magnetic resonance and high-resolution electrospray ionization mass spectrometry, and their configurations were subsequently confirmed by nuclear overhauser effect spectroscopy and the calculated electronic circular dichroism (ECD) spectra and quantum chemical calculations of the NMR data (qcc NMR). Based on the results of pre-activity screening and compound structure target prediction, certain metabolites were assayed to evaluate their cytotoxic and protein kinase Cα inhibitory activities. Results indicated that 3β-hydroxy-7α-methoxy-5α,6α-epoxy-8(14),22E-dien-ergosta (8) exhibited potent cytotoxic activity, with half-maximal inhibitory concentration values of 3.00 ± 0.27 to 15.69 ± 0.61 μM against five tumor cells, respectively. The new compound gunniiol A (1) showed weak cytotoxic activity at a concentration of 40 μM. At a concentration of 20 μg/mL, compounds 1, 6, and 7 exhibited protein kinase Cα inhibition by 43.63%, 40.93%, and 57.66%, respectively. This study is the first to report steroids demonstrating good cytotoxicity and polyketides exhibiting inhibitory activity against protein kinase Cα from the extracts of P. gunnii.